Moral Economy and Emancipation - Richards, H (Taylor and Francis Ltd., 2020)
Andrew Sayer and Dave Elder-Vass are both advocates of ‘moral economy’. To this end, Elder-Vass offers a theory of appropriative practices that enables us to evaluate the enormous variety of forms of provisioning–market and non-market–that are actually found in the world. Andrew Sayer, in the view of the present author, has devoted himself to correcting a great historical error. The error has been trying to do radical political economy without explicitly proposing normatively superior alternatives that are based on objective ethics committed to meeting needs and diminishing suffering. There follow five suggestions regarding how to integrate moral economy with the views on emancipation expressed in early Bhaskar. Perhaps the most important of these suggestions is that to achieve emancipation, rather than over-emphasising relations of production, we should instead identify–in order to, if necessary, transform–the deep moral and legal structures that frame markets. © 2020, © 2020 Informa UK Limited, trading as Taylor & Francis Group.